How I wonder what you are: Can DNA barcoding identify the larval asteroids of Panama?. Issue 4 (16th December 2020) - Collin, Rachel; Venera‐Pontón, Dagoberto E.; Driskell, Amy C.; Macdonald, Kenneth S.; Boyle, Michael J.
Abstract: As part of a project to document the diversity of larval invertebrates on both coasts of Panama, we collected and photographed 141 larval asteroids and sequenced fragments of their mitochondrial cytochrome c oxidase subunit I ( COI ) and 16S ribosomal DNA. We uncovered 10 Caribbean operational taxonomic units (OTUs) and five Pacific OTUs. We could identify six of the 15 OTUs based on >99% similarity with reference sequences in GenBank: The Pacific species Astropecten verrilli and Pentaceraster cumingi and the Caribbean species Astropecten marginatus, Astropecten antillensis, Oreaster reticulatus, and Mithrodia clavigera . Two other OTUs were placed in BINs in the Barcode of Life Database (BOLD) with unpublished sequences that were identified as Pharia pyramidata from the Pacific and Valvaster striatus, now known from the Caribbean as well as the Indo‐West Pacific. The remaining seven species appear likely to belong to Luidia, as 16S sequences from each have 87%–95% identity with various species of Luidia, and the sequences nest among species of Luidia in neighbor‐joining trees. The low diversity of asteroid larvae reflects 10% of the diversity of adult sea stars reported from Panama, and highlights the need for broader collection efforts and improved coverage of DNA barcode reference sequences for Luidia and other soft‐bottom species.